2022
DOI: 10.1007/s10238-022-00871-8
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q10 + alpha lipoic acid for chronic COVID syndrome

Abstract: Chronic COVID syndrome is characterized by chronic fatigue, myalgia, depression and sleep disturbances, similar to chronic fatigue syndrome (CFS) and fibromyalgia syndrome. Implementations of mitochondrial nutrients (MNs) with diet are important for the clinical effects antioxidant. We examined if use of an association of coenzyme Q10 and alpha lipoic acid (Requpero®) could reduce chronic covid symptoms. The Requpero study is a prospective observational study in which 174 patients, who had developed chronic-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 74 publications
0
10
0
Order By: Relevance
“…This indicates that Lipoic Acid could perturb the CD68.N gene set by affecting the DNA methylation levels of IL6 and IL10, two key markers in cytokine storms related to COVID-19. Lipoic Acid has also been proven to have beneficial effects on COVID-19 severity by inhibiting the overproduction of reactive oxygen species (ROS) and inflammatory cytokines [10, 11].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that Lipoic Acid could perturb the CD68.N gene set by affecting the DNA methylation levels of IL6 and IL10, two key markers in cytokine storms related to COVID-19. Lipoic Acid has also been proven to have beneficial effects on COVID-19 severity by inhibiting the overproduction of reactive oxygen species (ROS) and inflammatory cytokines [10, 11].…”
Section: Resultsmentioning
confidence: 99%
“…While this list of metabolites serves as potential biomarkers for the disease, it also highlights a group of modulators for regulating the severity of or treating COVID-19. Several top-ranked nutraceuticals, such as lipoic acid [10, 11], N-acetyl-D-glucosamine [21], calcitriol (vitamin D3) [22], vitamin A/tretinoin [23], and spermine [24], have been suggested to have beneficial effects when used in symptom management and treatment of COVID-19.…”
Section: Resultsmentioning
confidence: 99%
“…It has complementary roles in damaged tissue associated with a strong antioxidant and anti-inflammatory effect. [39,40] The processes participating included reversing MTX-induced testicular damage, as marked with decreased iNOS and TNF-α immunoreactivity. In addition, ALA reversed MTXinduced inflammatory hints because it notably reduced the level of TNF-α, which is consistent with the earlier stated antioxidant/anti-inflammatory effects of ALA. [20] Other studies have also shown that ALA has anti-inflammatory effect by decreasing the level of TNF-α.…”
Section: Discussionmentioning
confidence: 99%
“…Since combinations of treatments might be beneficial, trials of a promising candidate therapeutic in combination with other compounds are needed. There are examples of small studies with such combinations that are indeed showing promise, including CoQ10 and Se [ 105 ] and CoQ10 and lipoic acid [ 106 ].…”
Section: Can the Focus On Long Covid Research Provide Benefit For Me/...mentioning
confidence: 99%